We Need to Talk About Corruption in Health Systems - Eleanor Hutchinson; Dina Balabanova; Martin McKee (Kerman University of Medical Sciences, 2019)
The health sector consistently appears prominently in surveys of perceived corruption, with considerable evidence that this has serious adverse consequences for patients. Yet this issue is far from prominent in the international health policy discourse. We identify five reasons why the health policy community has been reluctant to talk about it. These are the problem of defining corruption, the fact that some corrupt practices are actually ways of making dysfunctional systems work, the serious challenges to researching corruption, concerns that a focus on corruption is a form of victim blaming that ignores larger issues, and a lack of evidence about what works to tackle it. We propose three things that can be done to address this situation. First, seek consensus on the scale and nature of corruption. Second, decide on priorities, taking account the importance of the particular problem and the feasibility of doing something about it. Third, take a holistic view, drawing on a wide range of disciplines.